2013
DOI: 10.4321/s1135-57272013000200006
|View full text |Cite
|
Sign up to set email alerts
|

Fiabilidad y validez del Copenhagen Burnout Inventory para su uso en España

Abstract: RESUMENFundamentos: El cuestionario Copenhagen Burnout Inventory (CBI) es de dominio público para la medida del síndrome de burnout, que está estructurado en tres subdimensiones: la personal, la relacionada con el trabajo y la relacionada con el trabajo con clientes. El objetivo de este trabajo es determinar la aceptabilidad, fiabilidad y validez de su traducción al español.Método: La población de estudio fueron 479 trabajadores de la enseñanza, trabajo social, sanidad e industria. Tras el proceso de traducció… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 15 publications
4
23
0
1
Order By: Relevance
“…There have since been studies completed using the CBI in anesthesiologists and critical care physicians, as well as EPs. These have yielded consistent, valid, and reliable results measuring burnout 3234…”
Section: Resultsmentioning
confidence: 77%
“…There have since been studies completed using the CBI in anesthesiologists and critical care physicians, as well as EPs. These have yielded consistent, valid, and reliable results measuring burnout 3234…”
Section: Resultsmentioning
confidence: 77%
“…Psychometric evaluation of the CBI in Spain among four different occupational groups (teachers, healthcare workers, industry workers, and social service staff) showed that this tool is a reliable tool for measuring occupational burnout. 10 Other studies in China, South Africa, New Zealand, Portugal, Brazil, Italy and Malaysia have also shown the validity and reliability of this tool. 11-17 Nevertheless, the validity and reliability of the CBI in other languages and cultures has yet to be determined.…”
Section: Introductionmentioning
confidence: 83%
“…[32] In another study, carried out by Molinero Ruiz et al . [33] on the psychometrics of the CBI among 479 workers in four organizations with different work groups, the items of the three subscales showed good consistency and homogeneity. Moreover, convergent validity of the Spanish version of CBI was confirmed in the 19-item scale of CBI.…”
Section: Discussionmentioning
confidence: 99%